Finite Process Structures - Smith, Pamela Z.; Fitzwater, D.R. (University of Wisconsin-Madison Department of Computer Sciences, 1974)
A finite graph model is defined to describe all the computations, finite or infinite, generated by a formally defined complex of interacting digital systems. The graph, called a finite process structure, is an abstraction which can be formulated and computed directly from system representations. Finite process structures have properties making them excellent tools for design analysis; in particular, the infinite variety of graphs describing the processes of a single system at all levels of detail arranges itself into a lattice--so it is possible to find desired characterizations algorithmically. Thus top-down hierarchical analysis of systems becomes a plausible goal. Within this context, a semantic theory of process structuring is initiated: a process definition is given, and compared to state-of the-art definitions of processes.